Network address management in MANETs using an ant colony metaphor (2011)
Address management is a critical network process, since any node wishing to join a network must first obtain an address. Network address management in a mobile ad-hoc network (MANET) is a particular challenge due to the unique operating conditions of such networks, their dynamic topology, and the events that take place inside them. This chapter presents a proposal for solving the address management problem in a MANET by applying the self-organization and emergency principles governing the behavior of social insect colonies, particularly ant colonies.